PENGARUH IMPLEMENTASI PROGRAM PEMBERDAYAAN DAN KEPEMIMPINAN TERHADAP KINERJA APARAT KELURAHAN : (Studi Kasus pada Distrik Muara Tami Kota Jayapura Provinsi Papua) - Tiurma Sinaga; Siswidiyanto Siswidiyanto; Fadillah Putra (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
Realizing the welfare and satisfaction of the community in services in the kelurahan as the spearhead of the regency/city regional government is strongly influenced by the performance factor of the kelurahan apparatus itself. So that the performance of the village apparatus needs to be improved with the factors that influence it. The purpose of this study was to measure and analyze the effect of the simultaneous implementation of the Empowerment and Leadership Program on the performance of the Village Apparatus in Muara Tami District, Jayapura City, Papua Province using explanatory survey research methods and quantitative approaches. The results of this study indicate that the results of the regression test calculation are that the Fcount value is greater than Ftable with data 19.613>3, 32. This means that the implementation of empowerment and leadership programs simultaneously has a positive and significant effect on the performance of urban village officials in Muara Tami District, Jayapura City, Papua Province.